People with intellectual disability and their risk of exposure to violence: Identification and prevention - a literature review - Starke, Mikaela; Larsson, Anneli; Punzi, Elisabeth (Journal of intellectual disabilities, 2025)
The aim of the literature review was to identify knowledge and knowledge gaps concerning risks of violence toward children, youth, adults and elderly with intellectual disabilities, and how risks can be identified and prevented. The research revealed that children, youths and adults labelled with intellectual disabilities are more exposed to violence than others and that the target group lack knowledge about risks of violence and what it means to be exposed to violence. It was also found that professionals who work with people with intellectual disabilities may lack knowledge about violence, and those who work with violence lack knowledge about intellectual disabilities. There is thus a need to further elaborate routines to identify exposure to violence, and to identify the target group and a need to create collaborative teams with professionals who have in-depth knowledge of violence, and those who have in-depth knowledge about the target group.